Telemedicine as the New Outpatient Clinic Gone Digital: Position Paper From the Pandemic Health System REsilience PROGRAM (REPROGRAM) International Consortium (Part 2) - Bhaskar, Sonu; Bradley, Sian; Chattu, Vijay Kumar; Adisesh, Anil; Nurtazina, Alma; Kyrykbayeva, Saltanat; Sakhamuri, Sateesh; Moguilner, Sebastian; Pandya, Shawna; Schroeder, Starr; Banach, Maciej; Ray, Daniel (Frontiers in Public Health, 2020)
Technology has acted as a great enabler of patient continuity through remote consultation, ongoing monitoring, and patient education using telephone and videoconferencing in the COVID-19 era. The devastating impact of COVID-19 is bound to prevail beyond its current reign. The vulnerable sections of our community endure a relatively higher burden during a pandemic. The need to provide continued medical care in the era of social distancing has catalyzed the rapid adoption of telemedicine. Telemedicine offers an opportunity to improve health systems delivery, access, and efficiency. This article critically examines the current telemedicine landscape and challenges in its adoption across various medical specialities. The current consortium provides a roadmap and/or framework, along with recommendations, for telemedicine uptake and implementation in clinical practice during and beyond COVID-19.